Study on sustainability of land resources in Dengkou County based on emergy analysis. (10th January 2018) - Zhang, Qibin; Yue, Depeng; Fang, Minzhe; Yu, Qiang; Huang, Yuan; Su, Kai; Ma, Huan; Wang, Yuhang
Abstract: Land is one of the basic resources and it is significant for the survival of human beings and the development of society. In the arid desert area where the ecological environment is fragile, land resource often faces the pressure from ecological degradation and economic development. Therefore, it is of great significance to study the sustainability of land resource, which is beneficial for the rational operation of the regional ecology economic system. The sustainability of land resources of Dengkou County, Bayannaoer, China was studied based on the social and economic statistics data and land use data from 1998 to 2015. The result showed that from 1998 to 2015, the impact of human exploitation activities on the land resource had been intensified and the area of cultivated land and construction land increased evidently. This change led to a slow but continuous decline of the sustainability of the land resources in Dengkou. Based on the research above, land use evolution of Dengkou in a hundred years under two different development strategies—efficiency dominant strategy and ecology dominant strategy was simulated using an improved cellular automata (CA) model built in this research. Emergy analysis was also performed based on the simulation results. The results showed that under the efficiency dominant strategy the economy would grow rapidly but the sustainability of the land resources would be damaged greatly. Under the ecology dominant strategy, the development of economy would be stagnant, while the sustainability of land resources would be maintained. The results of the study indicated that the maintaining of the sustainability of land resources and the development of economy should be achieved simultaneously by industrial upgrading and technological innovation, while simple industrial expansion will lead to a decline in the sustainability of land resources.